Pengaruh Gaya Kepemimpinan Transformasional, Kompetensi, dan Kerjasama Tim Terhadap Kinerja Pegawai BUMDes Gemilang Desa Ketajen Gedangan Sidoarjo - Rifanda Putri; Tri Andjarwati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research tries to test whether transformational leadership style, competence and teamwork partially or simultaneously have an influence on the performance of BUMDes employees in Gemilang Village Ketajen Gedangan Sidoarjo. The sample of respondents in this research was 41 people. The data collection method used was through distributing questionnaires. Multiple linear regression analysis is a technique used to analyze data. These findings explain that there is a partially significant relationship between the transformational leadership style variable and employee performance, the competency variable and employee performance, and the teamwork variable. Employee performance is influenced by the variables of transformational leadership style, competence, and teamwork simultaneously. Furthermore, looking at the analysis of the R2 coefficient of determination, the R2 value (or R square) has an influence of 49.8%, and the remaining 51.2% is influenced by other variables.